In-silico screening of small compounds against Lassa fever haemorrhagic virus nucleoprotein - Ekpo Eyo Antai; Uwem Okon Edet; Elizabeth N. Mbim; Ini Ubi Bassey; Sozan M. Abdelkhalig; Francisca O. Nwaokorie; Ehssan Moglad; Jamda Ponmak; Samia Al-Shouli; Sawsan AlShouli; Destiny E. Charlie; Mohnad Abdalla (Scientific Reports)
Abstract Lassa fever hemorrhagic virus (LFHV) outbreaks in Nigeria continue to increase. With the possibility of a potentially deadly pandemic and the absence of a vaccine, an effective candidate drug that presents with no adverse effects and better clinical outcomes is urgently needed; hence, the aim of the study. Retrieved ligands: 5-(Methylene) evodiamine, N-(2-Fluorobenzoyl) evodiamine, N-[[2-(3-chlorophenyl)-5-(trifluoromethyl) pyrazol-3-yl]methyl]-2-(1-methyl-2,3-dihydroindol-5-yl) propanamide (NCTPMMDP), lauric acid, and sofosbuvir, and the target protein, 3MX5, were prepared and utilised for docking, molecular dynamics simulation, ADMET profiling, and DFT using standard protocols. The docking score for lauric acid was the lowest, with a value of − 6.1, followed by the standard drug and co-crystal control drug with scores of − 9.1 and − 8.9 kcal/mol, respectively. On the other hand, the scores of the other ligands ranged from − 9.5 to − 12.3 kcal/mol. Molecular simulations revealed fluctuations in the RMSD and RMSF values; however, overall, the formed complexes were stable during most of the docking simulation runs. Principal component analysis (PCA) analysis showed that all the ligands, apart from lauric acid, showed better conformational changes within the backbone of the protein. ADMET profiling showed that the ligands were better oral drug candidates than sofosbuvir, as revealed by their better absorption values and absolute compliance with the Lipinski rule of five. The DFT result showed that, apart from lauric acid, all the test ligands possess small energy gaps indicative of high reactivity. Put together, these findings indicate that the test ligands possess anti-LHFV potential that merits further in vivo and in vitro evaluations.